Women's Communication Strategy in Realizing Equality in Pesantren Darussalam: Analysis in the Perspective of Gender Performativity - Sumadi, Sumadi; Lilis Nurteti (al-Afkar, Journal For Islamic Studies, 2024)
This research examines the gender equality communication strategies employed by women at Darussalam Islamic Boarding School, utilizing Judith Butler's theory of gender performativity (1990) as a framework. Gender performativity in educational institutions signifies a proactive effort to attain equality in leadership, education, commerce, and decision-making. Women now hold public and authoritative positions equivalent to men due to their active participation. The changing communication styles of female leaders signify the dissolution of patriarchal authority and customs in Islamic boarding schools. Despite patriarchal leadership, gender equality is progressing. The rise of women's leadership, scientific expertise, and business management within the institution signifies inclusive governance.  The transformation of gender roles in educational institutions is altering internal dynamics and motivating students and future generations to prioritize equality and inclusion. This gender role shift in school is changing internal dynamics and inspiring students and the next generation to value equality and inclusion. The institution promotes gender equality and balance in traditional Islamic education. The regeneration of Darussalam Islamic Boarding School preserves these progressive values, creating a dynamic, inclusive educational tradition. This study shows that inclusiveness requires constant effort and adaptation, and communication strategies are crucial to gender equality. For women to fully participate in public and educational spaces, structural and cultural changes are needed to achieve gender equality in traditional spaces.